2001
DOI: 10.1207/s15328015tlm1303_5
|View full text |Cite
|
Sign up to set email alerts
|

Error Patterns of 3rd-Year Medical Students on the Cardiovascular Physical Examination

Abstract: These data suggest fundamental inadequacies in the current paradigm for teaching physical examination skills. Standardized patient checklist data can provide an informative window into the efficacy of teaching practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[7][8][9][10][11][12] Our study highlights the consequences and suggests that many adverse events are preventable. Our survey suggests that the major cause for error is simply that the examination is not performed.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[7][8][9][10][11][12] Our study highlights the consequences and suggests that many adverse events are preventable. Our survey suggests that the major cause for error is simply that the examination is not performed.…”
Section: Discussionmentioning
confidence: 76%
“…Our survey suggests that the major cause for error is simply that the examination is not performed. 12,13 In addition to diagnostic consequences, approximately half of the vignettes report treatment consequences. Most oversights pertained to a limited number of overlookers, suggesting that some errors may be remedied if several people examine the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is a selection bias, as the participation was voluntary and we were only able to recruit 50,6% of final year students at our clinic at that time. These data suggest that severe deficits in physical examination skills can be found not only in the early clinical education of medical students [2], but persist during finalyear medical education, uncovering an urgent need to enhance the examination skills of final-year medical students. This might be achieved using different approaches: (1) standardizing physical examination instructions throughout the faculty and providing these standards in written form to all students [5]; (2) broadening the offer in examination skills training through multimedia contents such as videos;…”
Section: All Itemsmentioning
confidence: 92%
“…However, several studies indicate that there are deficiencies in students' physical examination competencies. In 3 rd -year medical students, it was shown that defined error patterns occur when testing physical examination skills on standardized patients, leading to possible false diagnosis in patients with shortness of breath and chest pain [2]. Furthermore, a study examining the integration and transfer of focused physical examination skills into complex clinical scenarios such as ward rounds equally revealed severe deficits [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, there is a paucity of curricula devoted to formal clinical skills instruction in US medical schools. [9][10][11][12][13][14][15][16][17][18][19] As academic faculty increasingly focus on their own clinical and research efforts, declining resources support bedside teaching and clinical skills development for medical students. [20][21][22][23][24][25] In response, the University of Washington School of Medicine (UWSOM) in 2001 implemented a competency-based curriculum (the Colleges program) designed to teach fundamental clinical skills at the bedside to 2nd-year medical students; this program has been described previously.…”
Section: Introductionmentioning
confidence: 99%